PENGARUH KEMASAN DAN LAMA PENYIMPANAN Acetobacter sp. RMG-2 DALAM BAHAN PEMBAWA TERHADAP POPULASI DAN PRODUKSI BIOSELULOSA DENGAN KONSENTRASI INOKULUM TERBATAS - Ruth Melliawati; Nuryati (The East Java Biological Society, 2011)
Bioselulosa or nata de coco is one food product that contains 25% fiber, which is very useful to support health, especially the digestive system. Along with the development of science and technology, raw material for making nata de coco become increasingly diverse as well as developing its usefulness for the wider interests. Inoculum became one of the things that are important in nata production process is also a determinant of product quality. This research was conducted to obtain information about the packaging is good for storing inoculum Acetobacter sp. RMG-2 in the carrier material and the efficiency of inoculum for the production bioselulosa. Two kinds of containers (straws and plastic bags) with two kinds of carrier material (cellulose pulp and CMC) are used. Storage of inoculum carried out for 20 weeks at 4° C. The measured parameter is the number of population, wet weight, dry weight and thickness as well bioselulosa pesentase minimal inoculum for the manufacture bioselulosa. Result, the inoculum in the CMC are packed using a straw is better than the plastic bag packaging, with a population of Acetobacter sp RMG-2 at 4.53 x 108 cells/ml, while in the plastic bag packaging population reached 3.5 x 107 cells/ml, respectively during storage was 20 weeks (five months). Bioselulosa production uses between 1–15 ml inoculum in 1250 ml of medium/tray of wet weight data obtained vary. With 1 ml of inoculum produced an average wet weight of 725 grams with a thickness of 0.6 cm. Research on the percentage of inoculum between 0.1 to 1.0%, showing that the use of 0.1% (in the CMC carrier materials for 8 weeks) can still be used for production with the average bioselulosa/100 ml of medium weight 31.45 grams wet, 1.6 g dry weight and thickness of 0.8 cm during the 7 days incubation. Investigation was still continuing to be carried out to get optimal results.